World bibliography of rice stem borers (International Rice Research Institute, 1991)
This comprehensive bibliography is the first of its kind on stem borers, an important pest of rice and a major cause of yield losses and lower production. The authors have accomplished a monumental task. The stem borers that infest rice all over the world belong to a complex comprising at least 20 lepidopterous and 2 dipterous species. Until now, no compilation of literature on any of them was available. Also, the voluminous literature on stem borers is scattered. This volume lists all references to stem borers that could be found in the world rice literature. It also provides descriptions and an identification key of the different species, explains the life history of stem borers, and discusses pest occurrence, crop damage, host plant resistance, and methods of control. An important section is the key word index that will enable users of the bibliography to locate background on specific topics quickly